Core Self-Evaluations and Innovative Behavior Among Micro-Entrepreneurs: The Mediating Effect of Proactive Personality - Purba, Debora Eflina; Paundra, Joshua (Psychological Research on Urban Society, 2018)
Given the key role that entrepreneurs play in a country’s economic growth, there is a need to study how entrepreneurs innovate for their firm’s survival. This study aims to investigate the mediating effect of proactive personality on the relationship between core self-evaluations (CSE) and innovative behaviors among micro-entrepreneurs in urban areas. The data were obtained from a survey administered to 307 micro-entrepreneurs in Jakarta, Indonesia and its surrounding cities. Data were tested using Hayes’ PROCESS macro in SPSS. The results showed that CSE was related positively to innovative behavior, and that proactive personality was also related to innovative behavior. Results also showed that proactive personality mediated the relationship between CSE and innovative behavior, whereby CSE led to proactive personality, which in turn influenced innovative behavior. Theoretical and practical implications of the findings are further discussed.